2005
DOI: 10.1590/s1516-35982005000100013
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho e composição corporal de frangos de corte alimentados com diferentes níveis de proteína e de aminoácidos ou com livre escolha das dietas

Abstract: RESUMO -Foi realizado um experimento com 600 frangos de corte (300 machos e 300 fêmeas) de 1 a 49 dias de idade. Foram usadas três dietas (D) experimentais, isoenergéticas (3.000 e 3.150 kcal EM/kg nas fases inicial e de crescimento, respectivamente), porém com diferentes níveis de proteína bruta (PB) e um dos quatro primeiros aminoácidos (AA) essenciais (Lis, Met+Cis, Tre e Trip): D1, (controle): 22%PB; D2, 24% de PB com AA 20% a mais que D1 (altaPB+20%AA) e D3: 20% PB e AA 12% a menos que D1 (baixaPB-12%AA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
14

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 10 publications
1
3
0
14
Order By: Relevance
“…During this period, birds consumed more feed when fed Low and Regular AA concentrations (p < 0.05) were fed, probably in an attempt to supply AA deficiencies. Broiler chickens offered free choice between two diets with different CP and AA levels presented similar performance as the control group (22% CP), by choosing diets with less protein, but rich in essential AA (Kolling et al, 2005). These results indicate that the birds regulated their feed intake according to their protein requirements.…”
Section: Effect Of Different Dietary Concentrations Of Amino Acids Onmentioning
confidence: 67%
See 1 more Smart Citation
“…During this period, birds consumed more feed when fed Low and Regular AA concentrations (p < 0.05) were fed, probably in an attempt to supply AA deficiencies. Broiler chickens offered free choice between two diets with different CP and AA levels presented similar performance as the control group (22% CP), by choosing diets with less protein, but rich in essential AA (Kolling et al, 2005). These results indicate that the birds regulated their feed intake according to their protein requirements.…”
Section: Effect Of Different Dietary Concentrations Of Amino Acids Onmentioning
confidence: 67%
“…The Mixed NP is an intermeditate program that prevents excessive dietary AA supply during the finishing phase, when broilers become less efficient and excessive nitrogen may have a negative effect (Kolling et al, 2005). The deamination of AA excess increases nitrogen excretion (Faria Filho et al, 2007) and the carbon chain is stored as fat (Leeson et al, 1996), which is unhealthy for human nutrition (Appel et al, 2005).…”
Section: Effect Of Different Dietary Concentrations Of Amino Acids Onmentioning
confidence: 99%
“…Para isso, é necessário conhecer o valor energético dos alimentos. Kolling et al (2005) relataram que o fornecimento de dietas altamente energéticas resulta em carcaças mais gordas, enquanto dietas com alto teor de proteína resultam em carcaças mais magras. Dietas com relações calórico-protéicas mais amplas (menos proteína) promovem maior consumo de energia ou baixa ingestão de proteína.…”
Section: Introductionunclassified
“…These results are different from the findings of Zuowei et al (2011), who showed that females housed at high density had poorer FCR and lower BW at 42 d of age. The lower BW of females (Kolling et al 2005) compared with males may explain why, in the case of females, increasing bird density and maintaining the same nutritional density did not affect performance.…”
Section: Resultsmentioning
confidence: 99%